Trends and problems of development of the world tourism - E. A. Frolova (Вестник университета)
Tendencies of development of world tourism, its positive and negative aspects have been examined. On the basis of statistical data, the main target audience has been identified, which will need to be guided by the producer of tourist services in the future. New opportunities in the tourism industry have been considered. Among the trends in the development of tourism have been considered, such as the emergence of new consumer groups, the shift of attention towards resource efficiency, the development of the digital economy, transport innovations, that affect the growth of passenger mobility. In addition to the prospects of dynamic development, the problems, that the industry will face in the coming years have been designated. The methods of reducing the negative impact of the tourism industry have been presented.